2011
DOI: 10.1016/j.mad.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Protection against age-dependent renal injury in the F344xBrown Norway male rat is associated with maintained nitric oxide synthase

Abstract: Age-dependent renal damage is influenced by genetic background and the Fisher344xBrown Norway (F344xBN) rat is resistant to glomerular injury. In vulnerable strains, a fall in renal nitric oxide synthase (NOS) contributes to age-dependent renal damage. Here, we investigated renal NOS in young (3 months) and old (30 months) male F344xBN to test the hypothesis that renal NOS is maintained in "protected" strains. We also examined if 6 months of renin-angiotensin system (RAS) blockade using angiotensin converting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This is unlikely to be a compensatory response since the increased nNOSβ in the 5/6AI KC does not replace the nNOS∝ in location or function [1,57]. We also recently reported that the senescent Fisher 344/ Brown Norway cross, which develop very mild glomerular damage, exhibits increases in nNOSβ before any falls in nNOS∝ [59]. We are currently investigating whether the increased nNOS β may play a causal role in the injury development.…”
Section: Nos Proteinsmentioning
confidence: 99%
“…This is unlikely to be a compensatory response since the increased nNOSβ in the 5/6AI KC does not replace the nNOS∝ in location or function [1,57]. We also recently reported that the senescent Fisher 344/ Brown Norway cross, which develop very mild glomerular damage, exhibits increases in nNOSβ before any falls in nNOS∝ [59]. We are currently investigating whether the increased nNOS β may play a causal role in the injury development.…”
Section: Nos Proteinsmentioning
confidence: 99%
“…Indeed, we have previously shown that aged Fischer 344 X Brown Norway (F344/BN) rats, while relatively protected from glomerulosclerosis, do demonstrate increased glomerular ischemia/atrophy, tubular atrophy and interstial fibrosis with age [Moningka et al 2010]. Furthermore, when these animals were treated late in life (between 24 and 30 months of age) with the ARB, losartan, this tubule-interstitial injury was prevented, relative to animals treated with the ACEI, enalapril or age-matched controls; although enalapril treated animals consistently showed lowered levels of injury relative to controls [Moningka et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when these animals were treated late in life (between 24 and 30 months of age) with the ARB, losartan, this tubule-interstitial injury was prevented, relative to animals treated with the ACEI, enalapril or age-matched controls; although enalapril treated animals consistently showed lowered levels of injury relative to controls [Moningka et al, 2010]. Therefore, it is possible that losartan, is a more effective modulatior of ANG II mediated cell signaling processes.…”
Section: Introductionmentioning
confidence: 99%
“…All three strains have age-related reductions in ability to secrete renin (2, 3, 15). On the other hand, the F344xBN rat, which maintains a robust salt appetite response with age, has less incidence of renal pathology (19, 43, 44, 45). Regardless, the waning ability of aging F344xBN rats to respond to body fluid challenges was due more to impairments in behavior than in kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Like the BN strain, the F344xBN rat has less age-related pathology (e.g., fewer tumors) than the F344 and SD strains (2, 32, 45), and also lives longer in absence of disease (13, 32). In addition, the F334xBN strain is less susceptible to hydronephrosis of the kidney (14, 31) and does not develop glomerular sclerosis (19), both of which may have consequences for studies of body fluid homeostasis. This work tests if the F344xBN strain has significant impairments in thirst- and salt appetite-related behaviors with age.…”
Section: Introductionmentioning
confidence: 99%